Michael J. Shapiro. War Crimes, Atrocity, and Justice. Cambridge: Polity Press, 2015. - Janine Hartman (Studies in 20th & 21st Century Literature, 2017)
Review of Michael J. Shapiro. War Crimes, Atrocity, and Justice. Cambridge: Polity Press, 2015.
Keywords: war crimes; justice